2016
DOI: 10.1002/stem.2377
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Stem Cell Trials Using Companion Animal Disease Models

Abstract: Studies to evaluate the therapeutic potential of stem cells in humans would benefit from more realistic animal models. In veterinary medicine, companion animals naturally develop many diseases that resemble human conditions, therefore, representing a novel source of preclinical models. To understand how companion animal disease models are being studied for this purpose, we reviewed the literature between 2008 and 2015 for reports on stem cell therapies in dogs and cats, excluding laboratory animals, induced di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
109
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 161 publications
(139 reference statements)
3
109
0
6
Order By: Relevance
“…Dogs develop many of the same inflammatory and autoimmune diseases as humans and thus clinical studies of stem cell therapy in these canine models can be particularly informative with respect to safety and potential efficacy, in time frames much accelerated compared to human studies [64].…”
Section: Discussionmentioning
confidence: 99%
“…Dogs develop many of the same inflammatory and autoimmune diseases as humans and thus clinical studies of stem cell therapy in these canine models can be particularly informative with respect to safety and potential efficacy, in time frames much accelerated compared to human studies [64].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the canine breed Dachshund is commonly afflicted with disc degeneration and disc herniation in a manner similar to humans (Hoffman and Dow, 2016). Like humans, afflicted canines can show back pain, impaired movement, or near paralysis.…”
Section: Successful Stem Cell Trials In Animalsmentioning
confidence: 99%
“…Like humans, afflicted canines can show back pain, impaired movement, or near paralysis. In several studies using mesenchymal stem cells injected into affected discs, treated canines showed improvement, including reduced pain, ataxia, improved reflexes, and neurologic-locomotory recovery although surprisingly there did not appear to be any ultrastructural changes as monitored by MRI (reviewed in Hoffman and Dow, 2016). This underscores the utility of using an animal model (canine or bovine Kraus et al, 2017) which are more similar to human and also indicates that the criteria for stem cell mediated clinical success of disc disease might be focused on alleviation of symptoms and recovery of normal activity rather than ultrastructural changes in the spine as assayed by MRI.…”
Section: Successful Stem Cell Trials In Animalsmentioning
confidence: 99%
“…Several diseases have been reported mainly in dogs, but also in cats, and include the chronic kidney disease (CKD) model. The majority of these studies, although uncontrolled, reported that MSCs are potential candidates for regenerating the damaged tissue, as reviewed by Hoffman and Dow [72]. …”
Section: Mesenchymal Stem Cells (Mscs) In Diabetic Nephropathy (Dn)mentioning
confidence: 99%